Δείξατέ μοι δηνάριον (Łk 20,24) – monety używane w Palestynie na kartach Ewangelii - Blajer, Piotr (The Biblical Annals, 2023)
Numismatics is one of the auxiliary disciplines of archaeology and history. It analyses coins from a historical, artistic and economic point of view. Thus, it allows an appreciation of the past. Understood in this way, numismatics can be equally helpful, both to biblical scholars and to anyone who reads the Bible. The names of various coins used in the time of Jesus often appear on the pages of the gospels. In many cases, those names remain incomprehensible today, to say the least. Some modern translations of the gospels renounce the literal translation of those terms and prefer to replace the unintelligible names of ancient monetary systems with phrases which are more comprehensible for the contemporary reader. In Polish historical, archaeological and biblical literature, it is quite difficult to come across an article or a study that would examine the various types of coins that appear on the pages of the gospels. The following study intends to fill that lacuna. It analyses the vocabulary used by the evangelist to present the coins used in Palestine in the time of Jesus. Thus, it contributes to explaining why each of the evangelists chose these particular terms at the expense of others. Ultimately, the study sheds some light on the Greek term νόμισμα (coin), which appears only once in the entire New Testament (Matt 24:19).